Odpowiedź :
[tex]a) \frac{3}{5}* \frac{2}{7} = \frac{6}{35} \\b) \frac{4}{5} * \frac{3}{8} = \frac{12}{40}\\c) \frac{3}{4} * \frac{8}{9} = \frac{24}{36} \\d) \frac{7}{15} * \frac{10}{21} = \frac{10}{45}\\e) 2 \frac{3}{4} * \frac{1}{2} = \frac{11}{4} * \frac{1}{2} = \frac{11}{8} \\f) \frac{5}{9} * 4 \frac{1}{10} = \frac{5}{9} * \frac{41}{10} = \frac{41}{18} \\g) 2\frac{1}{2} * 5 \frac{1}{3} = \frac{5}{2} * \frac{16}{3} = \frac{40}{3} \\[/tex]
[tex]h) 3\frac{3}{4} * 4\frac{1}{5} = \frac{15}{4} * \frac{21}{5}= \frac{63}{4}\\i) 5\frac{6}{7}* 4\frac{2}{3}= \frac{41}{7}*\frac{14}{3 }= \frac{82}{3}\\j) \frac{4}{5}*\frac{2}{9}*\frac{6}{7}*\frac{7}{8}=\frac{48}{360}\\k) \frac{4}{7}*1\frac{3}{4}*3\frac{1}{2}= \frac{4}{7}*\frac{7}{4}*\frac{7}{2}= \frac{7}{2}\\l) 1\frac{5}{8}*3\frac{1}{5}*\frac{2}{26}= \frac{13}{8}*\frac{16}{5}*\frac{2}{26}= \frac{52}{130}[/tex]